Weak Gravitational Lensing Analysis of a Large Sample of Massive Galaxy Clusters - Anirut Phriksee (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
Weak gravitational lensing is an efficient technique to detect galaxy clusters and to probe their mass distribution. Galaxy clusters are the most massive gravitationally bound systems in the Universe, and their study provides important information about the formation of cosmic structures and the cosmological parameters. In this thesis we present a weak gravitational lensing analysis of a large sample of galaxy clusters. We have used the data from the Canada France Hawaii Telescope Legacy Survey (CFHT-LS) to obtain the mass measurement of 1342 galaxy clusters from the photometric catalog of Wen et al. (2012), located in the redshift range 0.1 < z < 0.8. From this very large dataset, we considered a set of 1176 galaxy clusters with robust weak lensing analysis and we have built a nearly complete sample of 50 optically rich clusters, which detailed study will be very valuable to investigate the dark matter distribution and the scaling relations. In particular, we have improved the color-color selection technique used to select background galaxies and we have used weak gravitational lensing to measure, for each galaxy cluster, the mass density radial profile, the total mass and the mass-to-light ratio (by comparing with the total luminosity of all the member galaxies). Our results show that the mass-to-light ratio is increasing with respect to the total mass of the clusters and the mean mass-to-light ratio of our sample of clusters is very viii close to mean cosmological value, as measured by the Planck satellite. These results also support the hypothesis that the dark matter is located mainly in the large halos of individual galaxy. Furthermore, this project is a preliminary step towards the next analysis of the weak lensing galaxy clusters in the surveys KiDS and VOICE, those are currently collecting data with the VLT Survey Telescope, in Chile.